(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this scientific article, methods of solving some trigonometric inequalities and proofs of identities using geometrical methods are shown. Teaching in such a style frames the reader with the beauty, charm, simplicity and ease of the procedure for solving the issue. Several variants of the proof of trigonometric identities are presented in the article, as a result of which the student’s knowledge, skills and ability to solve algebraic issues using the properties of geometrical forms are further formed. In addition to the Pythagorean theorem, the formula of the surface of a triangle, the inner and outer drawn circles of a triangle, as well as the Karno formula, were used to prove trigonometric identities. It is possible to recommend the following teaching methods in the article so that they can be used as a methodological guide in school and academic high school lessons.